Immune Modulation by Plasmid DNA-mediated Cytokine Gene Transfer - Piccirillo, C.A.; Prud'homme, G.J. (Current Pharmaceutical Design, 2003)
Autoimmune diseases frequently develop as a result of an abnormal activation of autoreactive T cells, excessive production of proinflammatory cytokines, particularly by CD4+ Th1 cells, and subsequent tissue destruction. Cytokine-dependent immunotherapy can be applied to alter the balance between Th1 and Th2 cell activity, or proinflammatory versus immunosuppressive cytokine profiles. Cytotoxic T lymphocyte (CTL) and / or macrophage activity can also be suppressed. Gene transfer offers numerous advantages for the in vivo delivery of cytokines or their receptors for immunotherapeutic use. We have relied on the injection of naked plasmid DNA into skeletal muscle to deliver therapeutic genes. In particular, we have successfully used this approach to deliver neutralizing cytokine receptors such as interferon γ (IFNγ)-receptor-Ig fusion proteins or anti-inflammatory cytokines such as transforming growth factor β-1 (TGF-β1) and interleukin 4 (IL-4). Intramuscular gene therapy is effective in protecting against several experimental autoimmune diseases including insulin-dependent diabetes mellitus (IDDM), experimental allergic encephalomyelitis (EAE), and systemic lupus erythematosus (SLE). Another promising approach involves DNA vaccination by plasmid-based codelivery of genes encoding an autoantigen and either a cytokine or other immunomodulatory molecule. Plasmid vectors offer interesting advantages over viral vectors, since they are simple to produce, nonimmunogenic and non-pathogenic. They can be repeatedly administered with relatively prolonged periods of expression in vivo, ranging from weeks to months after each injection. Plasmid-based intramuscular gene transfer has great therapeutic potential in the areas of autoimmune and inflammatory disorders.
Keywords: Plasmid